Diminished heart beat non-stationarities in congestive heart failure - Camargo, Sabrina; Riedl, Maik; Anteneodo, Celia; Wessel, Niels; Kurths, Jürgen (Frontiers in Physiology, 2013)
Studies on heart rate variability (HRV) have become popular and the possibility of diagnosis based on non- invasive techniques compels us to overcome the difficulties originated on the environmental changes that can affect the signal. We perform a nonparametric segmentation which consists of locating the points where the sig- nal can be split into stationary segments. By finding stationary segments we are able to analyze the size of these segments and evaluate how the signal changes from one segment to another, looking at the statistical moments given in each patch, for example, mean and variance. We analyze HRV data for 15 patients with congestive heart failure (CHF; 11 males, 4 females, age 56 ± 11 years), 18 elderly healthy subjects (EH; 11 males, 7 females, age 50 ± 7 years), and 15 young healthy subjects (YH; 11 females, 4 males, age 31 ± 6 years). Our results confirm higher variance for YH, and EH, while CHF displays diminished variance with p-values < 0.01, when compared to the healthy groups, presenting higher HRV in healthy subjects. Moreover, it is possible to distinguish between YH and EH with p < 0.05 through the segmentation outcomes. We found high correlations between the results of segmentation and standard measures of HRV analysis and a connection to results of detrended fluctuation analysis. The segmentation applied to HRV studies detects aging and pathological conditions effects on the nonstationary behavior of the analyzed groups, promising to contribute in complexity analysis and providing risk stratification measures.